Co-delivery of baicalein and doxorubicin by hyaluronic acid decorated nanostructured lipid carriers for breast cancer therapy. (3rd May 2016) - Liu, Qian; Li, Jia; Pu, Gaobin; Zhang, Fang; Liu, Hongyan; Zhang, Yongqing
Abstract: Purpose : Combination anticancer therapy is promising to generate synergistic anticancer effects, to maximize the treatment effect and to overcome multi-drug resistance. Nanostructured lipid carriers (NLCs), composed of solid and liquid lipids, and surfactants are potentially good colloidal drug carriers. The aim of this study is to construct a hyaluronic acid (HA) decorated NLCs as nanocarriers for co-delivery baicalein (BCL) and doxorubicin (DOX). Methods : BCL- and DOX-loaded NLCs (BCL/DOX-NLCs) were prepared. HA ligands were used for the decoration of BCL/DOX-NLCs to form HA decorated BCL/DOX-NLCs (HA-BCL/DOX-NLCs). The in vitro cytotoxicity studies of different formulations were evaluated on DOX drug-resistant MCF-7 breast cancer cell line (MCF-7/ADR cells). In vivo anti-tumor effects were observed on the murine bearing MCF-7/ADR cells model. Results : HA-BCL/DOX-NLCs showed highest cytotoxicity and synergistic effect of two drugs in tumor cells in vitro . The in vivo study revealed the greatest anti-tumor activity than all the other formulations in the murine breast cancer model. Conclusions : HA decorated NLCs could be used as a novel carrier to co-delivery BCL and DOX for breast cancer therapy. HA-BCL/DOX-NLCs could be a promising targeted and combinational therapy nanomedicine.